Dampak Kekerasan Fisik Dalam Hubungan Pacaran Pada Remaja Dan Solusinya - Alyya Putri Ryani; Asep Suherman (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
Physical violence in dating relationships among teenagers is an increasingly concerning phenomenon that can have serious impacts on the physical and psychological health of the victims. This research aims to examine the impact of physical violence in dating relationships among adolescents, from psychological, social, and emotional development perspectives. The common psychological impacts experienced by victims include depression, anxiety, lowered self-esteem, and long-term trauma that can affect their emotional development and behavior in adulthood. In addition, this violence also poses risks of social isolation, distrust in interpersonal relationships, and disruptions in the educational process. The proposed solutions in this research include prevention efforts through sexuality education and healthy relationships among adolescents, as well as raising awareness about the dangers of violence in dating relationships. In addition, psychological support and assistance for victims is also an important step in their recovery, both through individual counseling and community support. The government and educational institutions are expected to play an active role in socializing prevention programs and providing easily accessible intervention services for teenagers experiencing dating violence.